Mid-lower bathyal benthic foraminifera of the Campos Basin, southeastern Brazilian margin: biotopes and controlling ecological factors - Sousa, Silvia Helena de Mello e; Passos, Raquel Fernanda; Fukumoto, Marina; Silveira, Ilson Carlos Almeida da; Figueira, Rubens Cesar Lopes; Koutsoukos, Eduardo A. M.; Mahiques, Michel Michaelovitch de; Rezende, Carlos Eduardo (Anuário do Instituto de Geociências, 2006)
Abstract